Competitive adsorption and reduced mobility: N-octane, CO2 and H2S in alumina and graphite pores. (1st December 2020) - Badmos, Sakiru B.; Islam, Naimul; Shah, Urvi; Striolo, Alberto; Cole, David R.
Abstract : Because gas injection into geological formations is a common technology deployed for enhanced oil recovery (EOR), it is important to understand at the molecular level the relations between competitive adsorption and fluid mobility at the single-pore level. To achieve such an understanding, we report here molecular dynamics simulation results to document structural and dynamical properties of n -octane confined in slit-shaped alumina and graphite pores in the presence of CO2 or H2 S. The substrates are chosen as proxy models for natural hydrophilic and hydrophobic substrates, respectively. It was found that CO2 and H2 S could displace n -octane from alumina but not from graphite surfaces. Analysis of the results demonstrates that more attractive n -octane – surface and weaker CO2 /H2 S – surface interactions in graphite compared to alumina are responsible for this observation. Regardless of pore type, the results suggest that adding CO2 or H2 S suppresses the diffusion of n -octane due to pore crowding. However, the mechanisms responsible for this observation are different, wherein preferential adsorption sites are available on the alumina surface for both CO2 and H2 S, but not on graphite. To contribute to designing advanced EOR technologies, possible molecular mechanisms are proposed to interpret the results. GRAPHICAL ABSTRACT: